RESPONSE OF SUNFLOWER TO DIBBLING TIME FOR YIELD AND YIELD COMPONENTS - Ahmad, Shahbaz; Fayyaz-ul-Hassan; Ali, Hakoomat; Um-e-Robab (Journal of Research (Science), 2005)
Sunflower can be a most suitable crop to bridge the gap between local production and consumption. Accurate determination of physiological maturity would be valuable for managing sunflower with respect to time of planting and its wider adaptability. The present study was contemplated to quantify the varying sowing time effects on sunflower yield. The experiment was conducted at the University of Arid Agriculture, Rawalpindi. The experiment was planted in a randomized complete block design in a split plot arrangement with five hybrids and six sowing dates. Hybrids differed significantly for head diameter, thousand seed weight, seed yield and biological yield while number of seeds remained statically non significant. However, sowing dates affected all parameters significantly. Early sowing produced heads of large size, gave maximum number of seeds per head and the highest biological yield. Crop sown on July 22nd produced the maximum seed yield and amongst hybrids, SF-187 gave the highest yield.